The Meaning of the Practicum in Initial Teacher Training: The Educational Value of Tutoring - Sepúlveda-Ruiz, María del Pilar; Mayorga-Fernández, María Josefa; García Vila, Elena (Walden University, 2026)
The theory-practice and practice-theory relationship is a fundamental axis in the learning of trainee teachers; therefore, the practicum must constitute the key element in their university training. The research described in this paper, in which students and teachers from the bachelor’s degrees in early childhood education and primary education programs at the University of Huelva in Spain have participated, has been carried out through a descriptive and interpretative qualitative study focused on case studies. This study highlights the need for greater communication between the work experience centers and the university and between the professionals who tutor the work experience period. It also points to a demand for greater professional training in relation to the tutoring of the practicum so that students have the opportunity to build their professional identity through shared action and reflection. It is necessary to continue studying and assessing a modification of the study plans where the practicum has a relevant weight throughout the initial university training.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Practicum; Qualitative study; Case studies; Reflective practice; Tutoring; Teacher training